Trends in the Development of Modern Corporate Management Practices and Models (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article analyzes the origin of corporate governance, the importance of corporate culture in the implementation of corporate governance, corporate governance models, and the national corporate model. Based on the analysis of the above theories and current business activities, concluding suggestions are presented.